Assessing the mitigation effect of deep tunnels on urban flooding: a case study in Guangzhou, China. Issue 4 (21st April 2019) - Huang, Huabing; Zhang, Lin; Liu, Lin; Wang, Xianwei; Wang, Xina; Pan, Cuilin; Wang, Dashan
ABSTRACT: There are growing demands of deep tunnels to mitigate the severe urban flooding by providing a large storage capacity for excess storm runoff. This study aims to assess the flooding mitigation effect of a deep tunnel system proposed in the old downtown of Guangzhou, China, and to quantify the flooding volume difference by two storm hyetographs, the Chicago curve and the Improved Huff curve. Results show that the flooding volume is significantly reduced by a minimum of 19% and a maximum of 42% under design storms of 10- and 0.5-year return periods, respectively, when the deep tunnel system is constructed. There is a distinct spatial pattern for the mitigation effect. The best mitigation is in the west and the immediate north of the main tunnel, whereas the east does not show significant mitigation. Moreover, the actual flooding risk is likely underestimated when the Chicago curve is employed to design the storms.